Risk-off Episodes and Swiss Franc Appreciation: the Role of Capital Flows - Irineu de Carvalho Filho (Swiss National Bank, Study Center Gerzensee, 2013)
During episodes of increased global risk aversion, or risk-off episodes, safe haven currencies such as the Swiss franc tend to appreciate. The immediate impact of a risk-off shock is an increase in net private inflows to Switzerland, mostly driven by a reduction in Swiss residents' net purchases of foreign debt securities and reduced foreign exposure by Swiss banks: Over several quarters, risk-off episodes also appear to be related to reductions in net FDI outflows by Swiss residents. Given that the bulk of capital movements related to risk-off episodes is driven by decisions of Swiss residents, capital flow management policies that discriminate based on the residency of the investor (capital controls) are not likely to be effective at reducing the impact of risk-off episodes. However, prudential policies that limit leveraging or foreign exposure by Swiss banks may diminish the volatility of capital flows during risk-off episodes.
Keywords: F32; F65; 330; Schweizer Franken; Abwertung; Reservewährung; Kapitalimport; Kapitalverkehrskontrolle; Schweiz